2021
DOI: 10.1038/s41419-021-03578-y
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial progenitor cells-derived exosomal microRNA-21-5p alleviates sepsis-induced acute kidney injury by inhibiting RUNX1 expression

Abstract: The role of microRNA-21-5p (miR-21-5p) in sepsis-induced acute kidney injury (AKI) has been seldom discussed. Therefore, the objective of this present study was to investigate the mechanism of endothelial progenitor cells-derived exosomes (EPCs-exos) in sepsis-induced AKI via miR-21-5p/runt-related transcription factor 1 (RUNX1) axis. miR-21-5p was downregulated and RUNX1 was upregulated in the kidney of cecal ligation and puncture (CLP) rats, and miR-21-5p targeted RUNX1. Elevation of miR-21-5p improved renal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…As for HK2, PKM2, LDHA, and GLUT1 proteins detection, GAPDH, another glycolytic enzyme (Liao et al, 2019), was used as the loading control. The present study showed no effect of miR-21-5p on GAPDH expression, as indicated by no statistical difference of gray value in different group, which was in consistence with previous studies that miR-21-5p inhibition or overexpression did not affect GAPDH expression (Huang et al, 2021;Zhang et al, 2021) As an important characteristic of metabolic reprogramming in tumor cells, the Warburg effect contrib- utes to growth, survival, and proliferation of cancer stem cells (CSCs) as well as enables the maintenance of the CSCs state (Vaupel et al, 2019). Tumorigenic cells with stem cell-like characteristics are regarded as CSCs, which have strong multi-directional differentiation potential and self-renewal ability (Ayob & Ramasamy, 2018;Hajizadeh et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As for HK2, PKM2, LDHA, and GLUT1 proteins detection, GAPDH, another glycolytic enzyme (Liao et al, 2019), was used as the loading control. The present study showed no effect of miR-21-5p on GAPDH expression, as indicated by no statistical difference of gray value in different group, which was in consistence with previous studies that miR-21-5p inhibition or overexpression did not affect GAPDH expression (Huang et al, 2021;Zhang et al, 2021) As an important characteristic of metabolic reprogramming in tumor cells, the Warburg effect contrib- utes to growth, survival, and proliferation of cancer stem cells (CSCs) as well as enables the maintenance of the CSCs state (Vaupel et al, 2019). Tumorigenic cells with stem cell-like characteristics are regarded as CSCs, which have strong multi-directional differentiation potential and self-renewal ability (Ayob & Ramasamy, 2018;Hajizadeh et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Epidemiological investigation indicated that three out of every million young adults and children suffer from OS, and the incidence reaches a peak at 11-15 years of age with six in every million children (Lu et al, 2020). Although much effort has been dedicated to OS therapy, the five-year survival and prognosis of OS patients remain unimproved, particularly for patients with recurrence, multidrug resistance, or lung metastasis, due to insufficient diagnosis at the early stage and ineffective therapeutic approaches (Zhang et al, 2018). Therefore, it is necessary to identify novel clinical prognostic biomarkers and investigate the potential molecular mechanisms of OS to develop more effective therapeutic strategies (Tu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, a number of exosomal proteins, miRNAs and lncRNAs have been reported to promote the progression of AKI. For example, Cao et al ( 14 ) found that exosomal miR-125b-5p deriving from mesenchymal stem cells (MSCs) could promote tubular repair by suppression of p53 in ischemic AKI; Zhang et al ( 23 ) indicated that endothelial progenitor cells-derived exosomal miR-21-5p could alleviate sepsis-induced AKI by inhibiting runt-related transcription factor 1 expression. However, the function of exosomes in AKI needs to be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs are a type of short endogenous non-coding molecules with about 18-25 nucleotides 154 . The dysregulation of miRNAs is closely related to the pathophysiological process of AKI 155 - 165 . For example, the level of miRNA-21 in AKI patients is more than five times higher than that in healthy persons.…”
Section: Mirna-21mentioning
confidence: 99%